Evaluation of Radiographers Experience and Knowledge Related to Estimation, Radiation Dose Comparation, and CT Parameters in Kota Medan, Indonesia - Wahyudi Ifani; Bambang Soeprijanto; J. Moekono; Nur Ainy Fardana4 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction: In patient examination, the role of a radiographer is very important especially in applying appropriate techniques and procedures to minimize exposure received by patients as needed or optimization. Given this, radiographer knowledge of CT parameters is very important, especially the impact on radiation and the quality of the image produced. Perception of the risk and estimation of CT radiation doses also need to be radiographer’s knowledge because in the service, radiographers are the most frequently interacted with patients.Purpose: To assess the opinion, experience and knowledge of radiographers regarding radiation risk and CT parameters in Kota Medan , Indonesia. Materials and Methods: a survey study was conducted on 33 radiographers from three hospitals in Kota Medan using a 60-question questionnaire consisting of three parts: characteristics, experience, and knowledge. Data were analyzed using Excell and SPSS version 25. Results: the calculation of 48 knowledge problem questions answered, the total value of each respondent is then calculated. Average knowledge value of respondents 56.3% (poor category) with correct value range 14 - 32 with an average value of 26.1 + 4.2. None of the respondents answered all the questions correctlyConclusion: the score of the radiographer’s knowledge of estimation, dose comparison and CT parameters is still low. Review of knowledge, training or further courses related to CT optimization techniques need to be attempted again in the hospital for radiographers.